1979
DOI: 10.1002/j.1538-7305.1979.tb02965.x
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Active Switched Capacitor Biquad Building Blocks

Abstract: Two closely related, low‐sensitivity, active switched capacitor filter topologies are presented. Each of these circuits comprises two operational amplifiers and at most nine capacitors. The topologies have been carefully constructed so that they are immune to the various parasitic capacitances normally present in switched capacitor networks. One filter topology is capable of realizing any stable biquadratic z‐domain transfer function, while the second one is only slightly less than fully general. Most commonly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(51 citation statements)
references
References 12 publications
0
47
0
1
Order By: Relevance
“…There is no charge transfer through the discharging of input sampling capacitors via the virtual earth node of the OTA to the OTA feedback capacitors. This means that a high loop-gain can be achieved with this filter construction compared to a standard charge-transfer technique [18].…”
Section: Charge-redistribution Sc Designmentioning
confidence: 96%
See 2 more Smart Citations
“…There is no charge transfer through the discharging of input sampling capacitors via the virtual earth node of the OTA to the OTA feedback capacitors. This means that a high loop-gain can be achieved with this filter construction compared to a standard charge-transfer technique [18].…”
Section: Charge-redistribution Sc Designmentioning
confidence: 96%
“…Fig. 8(b) shows the equivalent single-ended noise model for the DITO, where again the only noise contributors are transistors and However, now acts as an input transistor in parallel with , and so the equivalent noise variance at the input of the DITO is (17) Assuming then the total equivalent input noise variance for both differential OTA's becomes whereas (18) From this, it can be concluded that the DITO produces a quarter of the noise power of the SITO, assuming that similar load capacitance, transistor geometries, and biasing currents are used.…”
Section: Amplifier Noise and Signal Rangementioning
confidence: 99%
See 1 more Smart Citation
“…10; the topology is that repor ted in (12) . This design has been adjusted for minimum capacitance spread and minimum total capacitance.…”
Section: Figurementioning
confidence: 98%
“…A variable second-order APF (KT2APF) has also been proposed [6] based on a PCA, in which the delay block is replaced by an APF consisting of the transfer function of KT1APF multiplied by z 1 . Those circuits do not require adjusting the dynamic range, and the peak value and the peak angular frequency of the band-pass delay of the KT2APF can be determined independently by the PCA.…”
Section: Introductionmentioning
confidence: 99%